Temperature, pH and sarcomere length of Caiman yacare in different body weight categories at slaughter - Melina Franco CORADINI; Gislaine Gonçalves OLIVEIRA; Sabrina Campos SBARAINI; Fernanda Losi Alvez de ALMEIDA; Maria Luiza Rodrigues de SOUZA (Revista Brasileira de Saúde e Produção Animal, 2023)
ABSTRACT The objective of this work was to characterize the internal temperature of the carcass, pH and sarcomere length in four categories of body weight at a slaughter. The categories were: category 1, animals up to 1.5 kg, category 2, animals from 1.501 to 2.5 kg, category 3, animals from 2.501 to 3.5 kg and category 4, animals over 3.501 kg. The time intervals evaluated were 0.5, 2, 4, 6, 8, 10, 12, 14, 16, 18, 24 and 36 hours after bleeding, therefore, a factorial scheme (4 x 12) was used, in which where four categories of pre-slaughter weight and the behavior of the carcasses during the post-slaughter time were evaluated. There was no interaction effect between the weight categories and the time for the variation of the carcass internal temperature, pH and sarcomere length, but when only the time of rigor was evaluated, there were significant differences for the analyzed parameters. The internal temperature of the initial average carcass (0.5 hours) was 16.02°C, reaching 3.80°C at 36 hours post-slaughter. In addition, the lowest average pH found was at 24 hours, with a value of 5.39. Regarding the sarcomere length, the smallest mean length observed was 1.41 µm at 16 hours post-slaughter and the final mean length (36 hours) was 1.89 µm. It was concluded that the analyzed margin of the categories of body weight at slaughter did not interfere in the variation of temperature, pH and sarcomere length during the post-mortem of the Pantanal caiman.